MOTIVASI BELAJAR DITINJAU DARI CLASSIONAL CONDITIONING THEORY: SEBUAH KAJIAN KONSEPTUAL [LEARNING MOTIVATION VIEWED FROM CLASSSIONAL CONDITIONING THEORY: A CONCEPTUAL STUDY] - Azmi, Wifaqul; Sa'adah, Nurus (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2023)
This research aims to explore learning motivation in terms of classical conditional theory. This research uses literature study. The result of this study is to view that the classical conditional theory sees learning motivation as the formation of habits by associating stronger and weaker stimuli, then the learning process occurs when there is interaction between individuals and the environment, and learning is making changes to individual by causing brain activity (called the unconditioned stimulus) and moving to learn (called the conditioned stimulus).